Hydropower licensing: a case study of Massachusetts' streamlined procedure - Gardiner, P. (Massachusetts Executive Office of Energy Resources, Boston (USA), 1980)
Licensing procedures for hydroelectric projects in Massachusetts are enumerated, reviewed, and evaluated. (LCL)